Islamic Education Management Strategy In Improving The Quality Of Teaching At MTs Al-Amiriyah - Ferdana Marantika; Moh Nur Fauzi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study aims to analyze the influence of teaching time management based on the principles of time management in Islam, the use of Islamic peer review methods, and spiritual learning environment innovations in improving the quality of student learning in MTs. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and document studies. Data were analyzed using thematic analysis techniques to identify patterns and relationships between research variables. The following is an adjustment of your research results to fit the request for a more detailed explanation of the method, including the number of participants, criteria, duration of observation, and data validation: The results show that the management of teaching time that follows Islamic principles, such as scheduling recitation activities on certain days such as Sunday Legi, increases student absorption through a more conducive learning atmosphere and inner peace. In addition, the Islamic peer review method based on the principles of deliberation (shura) and counsel (nashihah) has been proven to improve the quality of teaching by correcting shortcomings and strengthening strengths through constructive and collaborative evaluation. This study uses a descriptive qualitative approach, with data collection techniques through participatory observation, in-depth interviews, and documentation studies. The number of research participants was 12 people, consisting of 6 teachers and 6 students in the MTS Alamiriyah environment. The criteria for selecting participants are based on active involvement in learning activities that integrate Islamic values, as well as a minimum of 1 year of experience in the environment. Observations and interviews were conducted for 2 months, with a frequency of field visits twice a week. Each interview session lasts between 45 to 60 minutes. For data validity, source triangulation was carried out (by comparing data from teachers, students, and school documentation), as well as member checking to ensure the accuracy of the researcher's interpretation of the respondent's statement. Innovations in the spiritual learning environment, such as spiritual assistance and daily dhikr, also play an important role in creating a more productive and meaningful learning atmosphere, by increasing student concentration, motivation, and character building. This study concludes that the integration of Islamic principles in learning management has a positive impact on the effectiveness of teaching and student development holistically, both intellectually and spiritually.